The strategic role of civil society organisations in handling climate change: A case of Riau in Indonesia. Issue 1 (July 2021) - Samnuzulsari, T; Kristanti, D; Susanto, H; Yudiatmaja, W E; Yunanto, M K; Meilinda, S D; Akbar, D
Abstract: Although many local civil society organisations (CSOs) involve in reducing the impact of climate change, the issue has been reported by a limited study. This paper addresses the gap by investigating the role of local CSOs in helping to anticipate the effect of climate change. This study looked into the case of Riau because it has many CSOs concerned with environmental problems. The objectives of this research are to classify the environmental CSOs in Riau and analyze their contribution to climate change resilience. Using a qualitative approach, the data were collected by using interviews on a series of participants, including CSO's activists, government officials, academicians, and community leaders. We reveal that local CSOs can be classified as conservation, advocation, empowerment, and conflict resolution. Along with their own and government programs, the CSOs have been contributed to tackling climate change by ensuring forest and peatland preservation. The theoretical and practical contributions of the study are elaborated.